Granny's clan : a tale of wild orcas - Hodson, Sally, 1950- (Dawn Publications, 2012)
"[A 100 year-old orca whale named Granny leads a clan of orcas near the Pacific Northwest in hunting, teaching young whales, and establishing a friendship with humans. Back matter expands on orca life, including their language, echolocation abilities, and family relations]"--Provided by publisher.